The Utilization Of Memrise Application In Improving Students’ English Vocabularies at SMPN 4 Marisa - Monalysa Laonga; Gusfin Maulidyawanti Moonti; Verenita Rahayu Tulus (Pusat Riset dan Inovasi Nasional, 2025)
This research aimed to determine the utilization of the Memrise application in improving English vocabulary among seventh-grade students at SMPN 4 Marisa. This research employed a qualitative approach involving 20 students selected through purposive sampling. Data were collected through observation and interviews students'.The results showed that the use of Memrise helped enhance the students' English vocabulary, such as its interactive features, such as visuals, repetition, and game-based activities, increased students' interest and motivation in learning. The improvements identified include five aspects: vocabulary mastery, spelling accuracy, learning motivation, pronunciation, and vocabulary retention. In addition, students gave positive responses to the use of Memrise, stating that it was enjoyable, easy to understand, and effective in helping them learn new words. Therefore, Memrise can be considered an effective digital learning medium for improving students’ English vocabulary.